Perceived controllability and fairness in performance evaluation - Schiehll, Eduardo; Landry, Suzanne (Review of Business Management, 2014)
<!–[if gte mso 9]> Normal 0 21 false false false FR-CA X-NONE X-NONE <![endif]–> We investigated the effects of environmental uncertainty, decentralization of decisions rights, and the use of subjective performance measures on managers’ perceptions of outcome controllability and performance evaluation fairness. Based on a survey of 339 middle- and upper- level managers, our results suggest that environmental uncertainty adversely affects perceptions of outcome controllability and that this effect is not moderated by the decentralization of decision rights. Our results also show a positive association between perceived controllability and performance evaluation fairness. Although we found no direct effect of the use of subjective performance measures on perceived performance evaluation fairness, it appears to moderate the positive effect of perceived controllability on fairness. We also show that the positive effect of the use of subjective measures may depend on contextual and job-related factors. The overall results underscore the need to consider the organizational context (environmental uncertainty and decentralization of decision rights) to investigate how performance measures affect perceived controllability and fairness. Because perceived controllability and fairness affect individual attitudes and behaviors within an organization, our results have important implications for the design and use of performance evaluation systems.